A Retrospective Review of Thiazolidinediones with Development of a Troglitazone Conversion Protocol - Cameron Lindsey; Maqual Graham; Julie McMurphy (The Scientific World Journal)
The objective of this paper was (1) to assess compliance with the National Veterans Affairs Guidelines for the use of troglitazone and rosiglitazone and (2) to develop and implement a conversion protocol that allows effective management of patients receiving troglitazone. A retrospective chart review was conducted to assess adherence to guidelines for all patients receiving troglitazone and rosiglitazone at the medical center. Appropriateness of therapy through indication evaluation, safety through alanine aminotransferase (ALT) monitoring compliance, and efficacy through hemoglobin A1c (HbA1c) changes were used to assess adherence. According to National Veterans Affairs (VA) Guidelines, 68% of troglitazone and 63% of rosiglitazone patients had an appropriate indication for the use of these agents. Baseline ALT levels were obtained in 40% of troglitazone and 71% of rosiglitazone patients. Full compliance with continual ALT monitoring was seen in 6 and 54% of patients, respectively. Goal HbA1c was achieved in 57 and 29% of patients, respectively. Of the 33 patients receiving troglitazone, 19 were converted to rosiglitazone therapy; 11 were maintained on current regimens without troglitazone, and 3 were lost to follow up. Adherence to guidelines needs to be reinforced, in particular, compliance with ALT monitoring. However, there were no reported cases of hepatotoxicity in the patients reviewed. Many patients did not achieve a HbA1c